2020
DOI: 10.1007/s00106-020-00877-2
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of a new active bone conduction hearing device with optimized geometry

Abstract: Implantation of a new active bone conduction hearing device with optimized geometry Bone conduction hearing implants S106 HNO • Suppl 2 • 2020 Discussion The dimensions of the BC-FMT are based on physical and technical requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 35 publications
0
24
0
2
Order By: Relevance
“…In September 2019, the manufacturer introduced a follow-up model (BCI 602) in Europe, with reduced FMT dimensions, that improved the bone fit in mastoids of children and young adults [34]. However, in certain cases, like very young children, 3D virtual preoperative planning is still recommended [35]. For another, new bone conduction implant it was shown that the average minimum bone thickness was thicker than both the maximum transducer depth of 3 mm and the 2.7 mm bone involvement of the osseointegrating fixation screws.…”
Section: Discussionmentioning
confidence: 99%
“…In September 2019, the manufacturer introduced a follow-up model (BCI 602) in Europe, with reduced FMT dimensions, that improved the bone fit in mastoids of children and young adults [34]. However, in certain cases, like very young children, 3D virtual preoperative planning is still recommended [35]. For another, new bone conduction implant it was shown that the average minimum bone thickness was thicker than both the maximum transducer depth of 3 mm and the 2.7 mm bone involvement of the osseointegrating fixation screws.…”
Section: Discussionmentioning
confidence: 99%
“…The upgrade gives the same power output for effective amplification, but with nearly 50% less drilling depth. The Bonebridge BCI 602 has the same audiological and medical criteria as the first-generation device [22,23].…”
Section: The New Bonebridgebci 602mentioning
confidence: 99%
“…The transition can also bend medially up to 30° to accommodate curvature of the skull. A smaller drilling depth reduces drilling time and reduces the likelihood of dura exposure, decreasing surgical time significantly; in addition, self-drilling screws simplify handling [22,24,25] . The most significant difference between the two models is the shape and size of the internal part, where the thickness of the BC-FMT has narrowed from 8.7 to 4.5 mm (Figure 3).…”
Section: The New Bonebridgebci 602mentioning
confidence: 99%
See 2 more Smart Citations